Ecotourists' perception of outdoor recreation service quality at Sungai Itek, Gopeng, Perak, Malaysia - Ab Aziz, Mohd Noorazlan (2016)
Tourism has been identified by the Malaysian government as one of the 12 potential areas to generate income in the National Key Economic Areas through the Economic Transformation Program.About RM 103.6 billion has been targeted by the government to be contributed by this industry toward the Gross National Income (GNI) by year 2020.Realizing the essential of tourism sector to the Malaysian economy and local community development ecotourism has been acknowledged as an important niche area for tourism industry in Malaysia.Ecotourism products in Malaysia are normally associated with outdoor recreation activities which are based on the existing cultural, historical and natural resources.However, there are concerns raised by the outdoor recreation industry itself on the sustainability of the natural resources. Similarly,there are also concerns on how excellent of service quality has been practiced in outdoor recreation activity to satisfy the clients (tourist or ecotourist).Moreover, it was undeniable that doing this commercialized outdoor recreation activities would lead to the issues of service quality since the nature of business are servicing. A poor quality of service would lead to the dissatisfaction of clients (tourist or ecotourist).Therefore, this study has been conducted to identify the service quality level of outdoor recreation activities at Sungai Itek, Gopeng, Perak as evaluated by ecotourists. This study has employed the Ecotourists Service Quality (ECOSERV) model to assess the perceived service quality level of both tangible and intangible aspects such as service quality and conservation of natural resources. This study was based on the Expectancy Disconfirmation Theory which is the result of satisfaction of a person (tourist or ecotourist)towards service quality was determined from the perception of expectation and perception of performance gaps analysis (Q=P-E). A total numbers of 376 ecotourists had completed the questionnaire distributed. The main analysis used in this study is descriptive analysis and paired sample T-test.The study showed that ecotourists who participated in three types of outdoor recreation activities such as land based, water based, cultural and historical based were satisfied with the perceived service quality. The overall findings had revealed positive gaps pattern in all 30 attributes in 6 dimensions of ECOSERV. This indicated that the levels of perceived service quality of ecotourists in outdoor recreation experience toward recreational sites at Sungai Itek, Gopeng, Perak had managed to meet their perception of expectation.Findings from this study are of practical use to the Government of Malaysia and several related tourism agency which are seeking empirical evidence regarding ecotourism and service quality issues. In addition, instead of focusing just on business and profit making, those parties could use this study as a reference towards the current issues, challenge and problems that literally occurred day by day regarding service quality and conservation issues. True to the philosophy of ecotourism, results from this study can give awareness to particular tourism agencies, local community, tourists and ecotourists toward fulfilling their moral obligation to help in preserving the quantity and quality of natural and historical resources.